Impact of nerve‐sparing posterolateral parametrial excision for deep infiltrating endometriosis on postoperative bowel, urinary, and sexual function. Issue 1 (20th January 2022) - Ianieri, Manuel Maria; Raimondo, Diego; Rosati, Andrea; Cocchi, Laura; Trozzi, Rita; Maletta, Manuela; Raffone, Antonio; Campolo, Federica; Beneduce, Giuliana; Mollo, Antonio; Casadio, Paolo; Raimondo, Ivano; et al.
Abstract: Objective: To evaluate the functional outcomes of nerve‐sparing surgery for deep infiltrating endometriosis (DIE) with or without posterolateral parametrectomy. Methods: A multicenter, observational, retrospective, cohort study was performed including all symptomatic women who underwent nerve‐sparing laparoscopic excision of DIE and preoperative and postoperative assessment of functional outcomes through validated questionnaires between April 2019 and March 2020. Women with posterolateral parametrial DIE (P‐group) and women with no parametrial involvement (NP‐group) were compared in terms of preoperative and postoperative functional outcomes related to pelvic organs assessed through validated questionnaires (KESS and GIQLI for bowel function, BFLUTS for urinary function, and FSFI for sexual function); pain symptoms at 3‐month follow up assessed through an 11‐point visual analogue scale (VAS) for dyschezia, dysmenorrhea, dyspareunia and chronic pelvic pain; surgical outcomes; and rate of urinary voiding dysfunction at 3‐month follow up. Results: One‐hundred patients were included: 69 in the P‐group and 31 in the NP‐group. Preoperative and postoperative values of questionnaires, pain symptoms, and postoperative complication rates were comparable between the two groups, except for postoperative dyspareunia and sexual dysfunction, which were statistically higher in the P‐group. Only patients in the P‐group experienced urinary voiding dysfunction, but no statistical significance was reached ( P  = 0.173). Conclusion: Posterolateral parametrectomy for DIE appears to be associated with a higher risk of postoperative dyspareunia and sexual dysfunction. Abstract : Despite a nerve‐sparing approach, posterolateral parametrectomy for deep infiltrating endometriosis is associated during postoperative course with a higher incidence of dyspareunia and sexual dysfunction.